Metáfora e infância: a metáfora na produção visual e nas experiências artísticas em artes visuais na educação infantil - Juliana Mendonça de Castro Palhares (2022)
Metaphor and Childhood is a dissertation about understanding metaphors as a fundamental mechanism to build new senses and meanings, using Lakoff and Johnson’s work as a framework for defining the concept of metaphor. It investigates the presence of metaphor and its manifestations in visual productions and in the artistic experimentations of children between 4 and 6 years of age, based on the analysis of their capability to build new ways to structure the experience and [re]build meanings.